Acute effects of combined cycling and plyometrics on vertical jump performance in active males - González-Mohíno, Fernando; Rodrigo-Carranza, Victor; Rodríguez-Barbero, Sergio; Turner, Anthony; González-Ravé, José María (Biology of Sport, 2023)
The aim of this study was to analyze the acute effects of high vs low-intensity cycling efforts, combined with plyometrics, on vertical jump performance. Twenty-four physically active men (mean ±SD: 23 ± 2 years, 72.1 ± 10.1 kg, 1.73 ± 0.07 m) were randomly divided into two groups: experimental group (EXP, n = 16) and control group (CON, n = 8). EXP competed 2 experimental trials in a random order: (a) short high-intensity interval exercise (HI + Plyo) [5 × 10 s of cycling (“all-out”)/50 s active rest] or (b) low-intensity continuous exercise (LO + Plyo) [5 min of cycling at 75% of the HRmax)], along with 3 × 10 plyometric bounds (drop jumps)/1 min rest between sets. CON used a preconditioning activity of 13 min of low intensity cycling at ~60% of HRmax. Both EXP interventions significantly increased (p ≤ 0.05) the countermovement jump (CMJ) height at 1 min, 3 min, 6 min and 9 min compared to baseline, while the CON remained unchanged. There were no significant differences in CMJ performance enhancement between HI + Plyo (largest 11.2% at 9 min) and LO + Plyo (largest 15.0% at 3 min) at any time-point, suggesting that the plyometric component may be most important, with HR recovery taking slightly longer following HI + Plyo. The findings suggest that CMJ performance can be enhanced following high or low-intensity cycling combined with plyometric preconditioning activities in active males, the optimum recovery period likely to be individual-specific.